Stability Assessment of a Small Islanded Power Network with High Penetration of Renewable Energy - Verma, D.; Rajakaruna, Sumedha; Johnson, T. (IEEE, 2014)
Electricity generation using renewable energy sources especially wind and solar photovoltaic is increasing rapidly and replacing fossil generation. The impact is more significant in small islanded networks which historically have relied on diesel engines for generation. Since wind and photovoltaic generation is intermittent and unpredictable, it becomes difficult to schedule and manage a small network with varying load demand. Therefore, conventional generation or some kind of energy storage is required to maintain the balance between total network generation and load demand. This paper presents a case study of a small islanded electrical network in Western Australia with various combinations of wind turbines, photovoltaic modules and diesel generators. It studies their impact on voltage and frequency stability of the network with a view to maximize the penetration of renewable energy.